Students' preferences for lecturers' personalities. Issue 3 (3rd April 2018) - Tan, Sarah; Mansi, Angela; Furnham, Adrian
Abstract: The present study set out to examine students' preferences for lecturers' personality as a function of their classroom behaviour, core self-evaluations and self-rated character strengths. Various hypotheses were tested: first, students' Big Five traits would significantly predict corresponding personality preferences for lecturers (the matching hypothesis); second, students' core self-evaluation scores would significantly predict preferences for extraverted, agreeable and conscientious lecturers; and third, self-rated character strengths would also significantly predict extraverted, agreeable and conscientious lecturers. We also investigated difference in preferences among two ethnic groups (South East Asian/Chinese versus Caucasian/British). In all, 264 British students completed four questionnaires. Conscientiousness was the most desired trait in lecturers, followed by agreeableness, extraversion and openness; neuroticism was the least desired trait. Preference for agreeable lecturers was best predicted by all individual difference variables. Caucasian students had a stronger dislike for neurotic lecturers, while Asians had higher preferences for extraverted, open and agreeable lecturers. There was some evidence of the student–lecturer personality match. Limitations and further research options were discussed.